2008
DOI: 10.3122/jabfm.2008.04.070092
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Supplemental Calcium Use Among Women in Suburban Family Practice: A Report from the Cleveland Clinic Ambulatory Research Network (CleAR-eN)

Abstract: Background:The majority of adult women in the United States fail to meet daily calcium intake recommendations. This study was undertaken to (1) identify predictors of calcium supplement use versus non-use, (2) understand barriers to calcium supplementation, and (3) determine the potential impact of physician recommendation on calcium supplement use.Methods: Surveys were self-administered by 185 women, ages 20 to 64, presenting consecutively for care at 6 suburban community-based family medicine practices withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…It should be mentioned that these differences can be due to the different life styles of Taiwanese, American and Iranian people. 6,33 The major limitation of this study can be referred as the closed list of supplements. In other words the name of supplement(s) was not designed as an open question, in fact, if the student had the experience of using supplement, s/he would mention the name of the supplement in the next question.…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that these differences can be due to the different life styles of Taiwanese, American and Iranian people. 6,33 The major limitation of this study can be referred as the closed list of supplements. In other words the name of supplement(s) was not designed as an open question, in fact, if the student had the experience of using supplement, s/he would mention the name of the supplement in the next question.…”
Section: Discussionmentioning
confidence: 99%
“…Even though, the increase in calcium intake and vitamin D was statistically significant with abnormal BMD measurements, overall the findings indicate that increasing generalized osteoporosis knowledge does directly influence calcium and vitamin D intake (Estok et al, 2007;Rolnick et al, 2001;Sedlak et al, 2005) suggesting that a lack of knowledge acts as a barrier and constrains participation with OPBs. This finding is also supported by a recent survey examining barriers to calcium supplementation for women 20-64 years of age, the survey suggested that one of the primary reasons women, 55% in this survey, have high rates of non-use of supplementation was not knowing it was necessary (Tyler et al, 2008).…”
Section: Osteoporosis Knowledge Gapsupporting
confidence: 70%
“…Calcium supplementation was also reported as a low priority in 77% of the non-users (Tyler et al, 2008).…”
Section: Osteoporosis Knowledge Gapmentioning
confidence: 99%
“…Besides, knowledge of osteoporosis was reported to influence calcium intake and exercise indirectly through self-efficacy among students [13]. Another study suggested that identifying the barriers to calcium supplement could be one of the strategies to increase their calcium intake and reduce osteoporosis risk [14]. The study found that the leading barrier for young adults to consume calcium supplements was the lack of knowledge about the importance of increasing calcium intake, the lack of motivation to start supplements, and the belief that their dietary calcium intake alone was sufficient.…”
Section: Introductionmentioning
confidence: 99%